Leveraging Smart Energy Meters for Precise Electricity Consumption Monitoring in Healthcare Facilities : (Rumah Sakit Tiara Sella, Kota Bengkulu, Provinsi Bengkulu) - Novalio Daratha; Hendy Santosa; Dedi Suryadi; Aji Arya Dewangga; Adhadi Kurniawan; Arie Vatresia; Firtrianty Wardhani (Dharmakayana, 2025)
The creation, transmission, distribution, and consumption of electrical energy are the first steps in the provision of electrical energy. The efforts that are made to conserve energy need to be continuously improved to supply electricity that is affordable. In order to conserve energy, it is necessary to have the backing of technology, laws, and legislation, in addition to applying behavioral discipline to those who utilize energy. To put it simply, a smart energy meter is one of the fundamental components of conservation technology. At the moment, the bulk of PLN's 67.6 million clients make use of traditional energy meters that are powered by electromechanical technology. The measuring device has not been incorporated with the technology that is associated with the internet of things (IoT). On the other hand, electronic items like televisions, washing machines, and air conditioners have started to adopt the Internet of Things and become smart devices. The integration of smart gadgets and smart meters enables the creation of an energy management system that can be used to the consumption and distribution of electricity in residential or commercial facilities. At Tiara Sella Hospital, which has a high monthly energy consumption, this community service project was carried out in order to measure the optimization of energy use and to determine opportunities for improvement. It is believed that the installation of this energy meter would result in improved and more reliable methods of measuring and estimating the amount of energy that is utilized within the hospital setting, which will allow for more sustainable optimization efforts.